2012
DOI: 10.2174/187152012802650048
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation and Anti-inflammatory Roles of Polyphenols as Anticancer Agents

Abstract: Cancers are the largest cause of mortality and morbidity in industrialized countries. Several new concepts have emerged in relation to mechanisms that contribute to the regulation of carcinogenesis processes and associated inflammatory effects such as the modulation of innate immune cells and adaptive immune cells that could infiltrate the tumor. In the tumor microenvironment, there is a delicate balance between antitumor immunity and tumor-originated proinflammatory activity, which weaken antitumor immunity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 239 publications
(295 reference statements)
0
59
0
1
Order By: Relevance
“…Neutrophil locomotion and chemotaxis is course of action for chemoattarction. [20] In this procedure, ferulic acid was examined for chemo-attractant potential and mean number of neutrophils attracted per field was noted against positive control-casein. Ferulic acid caused increase in number of neutrophils attraction per field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutrophil locomotion and chemotaxis is course of action for chemoattarction. [20] In this procedure, ferulic acid was examined for chemo-attractant potential and mean number of neutrophils attracted per field was noted against positive control-casein. Ferulic acid caused increase in number of neutrophils attraction per field.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 0.1 ml of PBS solution (control) and 0.1 ml of endotoxin-activated plasma (standard) were added to first and second tubes, respectively, and to the other tubes were added 0.1 ml of different concentrations (10,20,40,100 and 1000 µg/ml) of ferulic acid. A total of 0.2 ml of freshly prepared 0.15% nitroblue tetrazolium (NBT) solution was added to each tube and incubated at 37°C for 20 min.…”
Section: Study Of Immunomodulatory Activity Qualitative Nitroblue Termentioning
confidence: 99%
See 1 more Smart Citation
“…The modulation of immune cells targeted for therapeutic intervention in malignant diseases may restore the sensitivity of cancer cells to chemotherapies. miRNAs should be analysed with nuclear factors, such as NF-κB, that serve as molecular links between inflammation and tumour progression [96]. …”
Section: Mirnas Related To Anti-tumour Immunitymentioning
confidence: 99%
“…Numerous studies have reported curative properties of dietary polyphenols such as curcumin, genistein, resveratrol, and epigallocatechin in cancer [ 64 ]. Micronutrients like zinc, selenium, and vitamin E have been shown to have immunoenhancing properties.…”
Section: Immunity and Infectionsmentioning
confidence: 99%